2010
DOI: 10.1111/j.1463-1318.2009.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of symptoms to predict colorectal cancer site. Can we reduce the pressure on our endoscopy services?

Abstract: Symptoms can accurately predict site of cancer, allowing investigations to be tailored accordingly. We would recommend that patients with altered bowel habit and/or rectal bleeding, and no other symptoms, risk factors or anaemia, can be investigated with a flexible sigmoidoscopy to confirm or refute a diagnosis of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
2
21
0
Order By: Relevance
“…A prospective cohort study by Thompson et 31 The findings of this study also supported the tailoring of initial investigations. In patients with CRC, distal lesions were associated with a CIBH and rectal bleeding.…”
Section: Tailoring Initial Investigations For Suspected Colorectal Casupporting
confidence: 78%
See 4 more Smart Citations
“…A prospective cohort study by Thompson et 31 The findings of this study also supported the tailoring of initial investigations. In patients with CRC, distal lesions were associated with a CIBH and rectal bleeding.…”
Section: Tailoring Initial Investigations For Suspected Colorectal Casupporting
confidence: 78%
“…28 It has been suggested that there is scope within the NHS to reduce the diagnostic burden for patients and endoscopy services by implementing clinical protocols which incorporate the selective use of FS, in place of WCI, for the initial investigation of patients with symptoms suggestive of distal CRC. [29][30][31][32][33] For WCI to be avoided in favour of FS, diagnostic protocols using FS for first-line investigation must be able to demonstrate INTRODUCTION NIHR Journals Library www.journalslibrary.nihr.ac.uk favourable risk-benefit profiles, in which the benefits of this less invasive procedure are balanced against the risk of a missed diagnosis of proximal cancer. [34][35][36] The use of such protocols is likely to be most relevant in clinical practice for which the clinical index of suspicion for proximal colon cancer is low, for example when patient and symptom profiles favour a diagnosis of distal CRC.…”
Section: Computerised Tomography Colonographymentioning
confidence: 99%
See 3 more Smart Citations